A note on “A Continuous Approach to Nonlinear Integer Programming” - Zhang, Guoqing (Applied mathematics and computation, 2009)
Ge and Huang (1989) proposed an approach to transform nonlinear integer programming problems into nonlinear global optimization problems, which are then solved by the filled function transformation method. The approach has recently attracted much attention. This note indicates that the formulae to determine a penalty parameter in two fundamental theorems are incorrect, and presents the corrected formulae and revised theorems.